Laccase Application in Medium Density Fibreboard to prepare a Bio-composite - Mohammed, Nasir; Gupta, Arun; Beg, M. D. H.; Chua, Gek Kee; Mohd, Asim (Royal Society of Chemistry, 2014)
Laccase efficacy as a biological tool for the removal of lignin in pulp industries is evident and has a scope for a wider application. In this research study, rubber wood (Hevea brasiliensis) fibres were treated with laccase enzyme to study its effect on the fibre surface and the enzyme hydrolysis lignin (EHL) was collected as a byproduct. Collected EHL was concentrated (con) till the solution reached a 3% solid content. Fibre surface modification was studied by FESEM, FTIR and XRD. A distinct fibre surface with an improved crystallinity index was observed. EHL and Con-EHL were analyzed on viscometer, FTIR, DSC, and TGA. Con- EHL exhibits a lower stretching energy at the benzene range as compared to EHL and a curing pattern similar to UF was reported. To evaluate the capability of modified fibre and Con-EHL, 6 mm medium density fibreboard (MDF) of 810 kg/m3 were prepared by using 10% Con-EHL solution (by weight of Page 1 of 31 RSC Advances RSC Advances Accepted Manuscript Published on 14 January 2014. Downloaded by RSC Internal on 03/02/2014 12:49:07. View Article Online DOI: 10.1039/C3RA40593Afibre). The MDF boards exhibit higher mechanical strength and have passed the ASTM D1037 standard for internal bonding and modulus of rupture.